بنية الشخصية في رواية وكالة عطية لخيري شلبي - جلايلية مريم (My University, 2024)
Summary Our study focused on the structure of characters in contemporary Arabic novels, specifically in the novel "Wakala Atya" by Khairy Shalaby. The aim was to identify the characters in the novel, their types and dimensions, and their relationships with other narrative components such as place and time. To achieve this, I divided my research into two chapters. The first chapter discusses the concept of character, its dimensions, and its types. The second chapter focuses on the internal and external structure of the characters in the novel. I also included an appendix where I talked about the author and provided a summary of the novel, relying on the structural method. Among the most significant findings was that the novelistic character is one of the most important narrative techniques in a novel and a crucial literary element, as no novel can exist without characters. ------------------- الملخص تمثلت دراستنا في بنية الشخصية في الرواية العربية المعاصرة في رواية "وكالة عطية" لخيري شلبي، والتي سعت لتحديد الشخصيات في الرواية وأنواعها وأبعادها، وعلاقاتها بالمكونات السردية الأخرى مثل المكان والزمان. ولهذا قسمت بحثي إلى فصلين الأول تطرقت فيه إلى مفهوم الشخصية، أبعادها وأنواعها، أما الثاني يتمحور حول البنية الداخلية والخارجية للشخصية في الرواية، وأرفقته ذلك بملحق تحدثت فيه عن الكاتب وملخص الرواية، معتمدين في ذلك على المنهج البنيوي، ومن أهم النتائج التي توصلت إليها ان الشخصية الروائية هي أحد أهم التقنيات السردية في العمل الروائي ومن العناصر الأدبية الهامة، فلا يمكن لأي رواية أن تقوم بدون شخصيات. -------------------- Résumé Notre étude portait sur la structure des personnages dans le roman arabe contemporain, en se concentrant sur le roman "Wakala Atya" de Khairy Shalaby. L'objectif était de définir les personnages du roman, leurs types et leurs dimensions, ainsi que leurs relations avec d'autres composants narratifs tels que le lieu et le temps. Pour cela, j'ai divisé ma recherche en deux chapitres. Le premier aborde le concept de personnage, ses dimensions et ses types. Le second se concentre sur la structure interne et externe des personnages dans le roman. J'ai également inclus une annexe où je parle de l'auteur et résume le roman, en m'appuyant sur la méthode structurelle. Parmi les résultats les plus significatifs, j'ai découvert que le personnage romanesque est l'une des techniques narratives les plus importantes dans une œuvre romanesque et constitue un élément littéraire crucial, car aucun roman ne peut exister sans personnages.
Keywords: character; novel; place; time; main character; الشخصية، الرواية، المكان، الزمان، الشخصية الرئيسية، الرواية.: personnage; roman; lieu; temps; personnage principal; roman.